Aspek Hukum Perlindungan Anak Atas Tindak Pidana Penganiayaan Yang Dilakukan oleh Orangtua Kandung - Helmy Zuhri (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to explain how the protection of children for criminal acts of persecution in the Karawang district, Child Protection is an activity that guarantees and protects children and children's rights so that they can live, grow, develop, and participate optimally in accordance with human dignity. and get protection from violence and discrimination based on Law Number 35 of 2014 concerning Child Protection. The crime against the body in the Criminal Code is called “Maltreatment”. Based on the analysis carried out, it was concluded that legal protection against criminal acts of child abuse in the Karawang district had been carried out properly by the Karawang district government but the implementation was less effective for the application of child protection law in cases that occurred in the community, making several elements - community elements feel that acts of abuse or violence against children are light actions whose punishments are also light so that the community's sensitivity to the protection of the child itself is reduced.